1996
DOI: 10.1007/bf02583277
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous haemorrhage and other ocular complications of a persistent hyaloid artery

Abstract: Abstract. Purpose: To report ocular complications of a persistent hyaloid artery. Methods: We studied eight patients with persistent hyaloid artery. Results: Seven patients showed strabismus and very low visual acuity (< 0.12) of one eye. Despite correction of refractive errors, cataract surgery and occlusion therapy for amblyopia, visual acuity had not improved in these cases. Four patients showed nystagmus. Four had progression of unilateral cataract. In two cases, a 24-year-old woman and a 4-months-old boy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…[14] For diagnosis, slit-lamp examination, fundus examination, fluorescein angiography (FAG), OCT and Doppler ultrasound have been used. [3-8, 13, 15] Gonçalves et al [4] and Chen et al [5] showed proximal filling. Our patient refused to FAG, so we took OCT angiography which was noninvasive to the patient in order to check the blood flow of the PHA.…”
Section: Discussionmentioning
confidence: 99%
“…[14] For diagnosis, slit-lamp examination, fundus examination, fluorescein angiography (FAG), OCT and Doppler ultrasound have been used. [3-8, 13, 15] Gonçalves et al [4] and Chen et al [5] showed proximal filling. Our patient refused to FAG, so we took OCT angiography which was noninvasive to the patient in order to check the blood flow of the PHA.…”
Section: Discussionmentioning
confidence: 99%
“…PHPV in humans typically presents as unilateral leukocoria and elongated ciliary processes in a microphthalmic eye . Hemorrhage in the anterior and posterior segments, progressive cataract, microphakia, secondary glaucoma, retinal detachment, and phthisis have been reported in affected human and canine eyes …”
Section: Introductionmentioning
confidence: 99%
“…Vidna oštrina na zahvaćenom oku je nepredvidiva [14][15][16][17]. A. hyaloidea može biti funkcionalna čak i u starijoj životnoj dobi, a da ne utiče na vidnu oštrinu [15].…”
Section: Introductionunclassified